Formation of a system of marketing metrics for assessing the level of customer satisfaction and loyalty - Churlei, Eduard G. (Journal of the Belarusian State University. Economics, 2022)
Changes in the competitive field and the speed of the course of events orient market players to the need to find ways to assess the level of satisfaction and loyalty. The current method is the introduction of a system of direct and indirect metrics based on a complex of marketing research, as well as the integration of this system with the customer journey map (CJM).